Pilgrimage and Economy in the Ancient Mediterranean - Collar, Anna (Religions in the Graeco-Roman World Ser., 2020)
Pilgrimage and Economy in the Ancient Mediterranean brings together diverse scholarship to explore the socioeconomic dynamics of ancient Mediterranean pilgrimage from archaic Greece to Late Antiquity, the Greek mainland to Egypt and the Near East.